Direct-Acting Oral Anticoagulants: A Resident-Based Workshop to Improve Knowledge and Confidence - Irsk Anderson; Vineet M. Arora (Association of American Medical Colleges, 2020)
Introduction Direct-acting oral anticoagulant (DOAC) prescriptions have increased steadily since the first, dabigatran, was Food and Drug Administration-approved in 2010. They have multiple advantages over vitamin K antagonists including fixed dosing without coagulation lab monitoring, rapid onset and offset of action, and fewer drug and food interactions. Patient-specific dosing, administration education, adherence, and monitoring are critically important. Many providers are unfamiliar with these concepts and too often use DOACs for off-label indications or at off-label dosing. A DOAC workshop was created to address knowledge gaps and improve internal medicine resident prescribing confidence. Methods One author (Irsk Anderson) conducted four 1-hour DOAC workshops with 49 total internal medicine residents rotating on their outpatient clinical rotation between October 2018 and November 2019. Residents performed small-group learning around four DOAC-specific cases, followed by a large-group report-out session. The residents completed pre- and postworkshop multiple-choice questions (MCQs) to assess knowledge as well as a postworkshop DOAC confidence self-assessment. Results Resident knowledge, assessed by percentage of residents answering correctly, improved significantly for all four MCQs after completing the workshop (all p <.003). Resident confidence, assessed on a 5-point Likert scale, improved significantly for all five themes (p <.001). Overall resident satisfaction was high (M = 4.2 on a 5-point Likert scale) and 85% desired further DOAC training. Discussion A 1-hour DOAC workshop was feasible and improved internal medicine resident knowledge and self-confidence. Future work should assess behavior change and patient clinical outcomes.